Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cells11010126
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan: A Neuroimmune Modulator in the Microbiota-Gut Axis

Abstract: The commensal microbiota plays a fundamental role in maintaining host gut homeostasis by controlling several metabolic, neuronal and immune functions. Conversely, changes in the gut microenvironment may alter the saprophytic microbial community and function, hampering the positive relationship with the host. In this bidirectional interplay between the gut microbiota and the host, hyaluronan (HA), an unbranched glycosaminoglycan component of the extracellular matrix, has a multifaceted role. HA is fundamental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…It is a ubiquitous transmembrane glycoprotein which acts as a receptor and regulates several interactions between cells and the extracellular matrix. Its isoforms are predominantly overexpressed in inflammation and cancer [ 22 , 226 ]. HA presents high affinity for CD44, in addition to pH-responsiveness.…”
Section: Resultsmentioning
confidence: 99%
“…It is a ubiquitous transmembrane glycoprotein which acts as a receptor and regulates several interactions between cells and the extracellular matrix. Its isoforms are predominantly overexpressed in inflammation and cancer [ 22 , 226 ]. HA presents high affinity for CD44, in addition to pH-responsiveness.…”
Section: Resultsmentioning
confidence: 99%
“…However, in non-injured and sham-operated groups, 4-MU treatment influenced bacterial intragroup composition. In particular, the reduced variability observed in samples obtained from non-injured animals, after 4-MU treatment, underlines the relevance of HA in maintaining gut bacteria homeostasis in normal conditions [ 52 ]. HA may also influence commensal bacterial variability after laparotomy, as suggested by the ability of 4-MU to restore α-diversity indexes in the sham-operated group.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract (GIT) hosts a pool of immune cells representing 70% of the entire immune system, and the largest population of macrophages in the human body [279]. Through its local immune system, the GIT detects and responds to the local microbiome [263], but also impacts upon remote immune processes [280][281][282][283][284][285][286][287][288][289][290][291][292][293][294][295]. During the past years multiple experimental studies have revealed that the microbiome and local immune system of the GIT may modulate distant inflammation within the cardiovascular system and brain [242,245,262,263,272,274,278,279,[296][297][298][299][300][301][302].…”
Section: Immune Impact and Therapeutic Perspectives Of The Intestinal...mentioning
confidence: 99%